Policy Making of Strategic Plan for Success of Five-Year Development Agenda of Local Governance - Taufiqurokhman, Taufiqurokhman; Andriansyah, Andriansyah (Universitas Malikussaleh, 2019)
The policy making of the five-year strategic plan of its substance, involves participation in the process of policy formulation through Development Deliberation discussion in decentralization of regional autonomy. That is, it delivers the authority of the central government to the autonomous regions in determining the policy (political authority) and implementing the policy (administrative authority), based on local voice and local choice. The local government is expected to identify needs, formulate development goals. The research used qualitative method with ethnography approach by collecting various data from various sources with deep-interview technique. The purpose of the study describes the three things, namely setting agenda, policy formulation and budgeting in a formulation of stakeholders' participation. For contribution: First: participation in development planning in tokenism and elitist party stages, partnerships between communities with bureaucracy and political officials are still subordinate union of partnership. Dialogue held is still pseudo and decision making are not done by bargaining among actors. Second: The quality of planning is still bad, because it has not been able to answer the needs of the community and there is no interconnected substance between documents with one another.